A profile of mathematics education doctoral graduates' background and preparation in the United States. (2nd January 2019) - Shih, Jeffrey C.; Reys, Robert E.; Reys, Barbara J.; Engledowl, Christopher
ABSTRACT: This landmark study of doctoral graduates in mathematics education provides benchmark data that we hope will be useful to the mathematics education community. Five hundred three doctoral graduates from twenty-three institutions participated in the study with a response rate of over 90 percent. This article focuses on doctoral graduate satisfaction with their doctoral preparation, the influence of full-time doctoral status, mathematics and mathematics education course requirements, and preparation to teach methods courses.